Evaluation of different feeds for nursery rearingof Asian seabass Lates calcarifer (Bloch) - Kailasam, M; Thirunavukkarasu, A R; Sundaray, J K; Abraham, Mathew; Subburaj, R; Thiagarajan, G; Karaiyan, K (Indian Journal of Fisheries, 2011)
Asian seabass, Lates calcarifer (Bloch) fry were reared with Artemia biomass,PUFA enriched Artemia, Moina, PUFA enriched Moina, egg custard and fishmeat as feeds. Survival and growth rates were recorded after 45 days of rearing.Maximum survival (88.7 ±4.1%) was observed in PUFA enriched Artemia,followed by non-enriched Artemia (85.33 ± 8.2 %), PUFA enriched Moina (84.0 ±6.5 %), non-enriched Moina (82.0±1.6%), egg custard (71.3±6.6%) and fish meat(60.3±5.7%). Mean length increment was 41.2 ± 4.0 mm in fry fed with PUFAenriched Artemia biomass, followed by non-enriched Artemia (41.0 ± 6.1 mm),non-enriched Moina (29.0 ± 3.0 mm), egg custard (28.6 ± 3.7 mm), enrichedMoina (26.8 ± 2.8 mm) and fish meat (22.3 ± 3.0 mm). However wet weight gainwas in the order of non-enriched Artemia (0.90 ± 0.03 g), followed by enrichedArtemia (0.86 ± 0.23g), egg custard (0.35 ± 0.1g), non-enriched Moina (0.31 ±0.06 g), enriched Moina (0.23 ± 0.09 g) and fish meat (0.14 ± 0.05 g). Resultshave indicated that Artemia biomass enriched with PUFA is a better feed forrearing seabass fry.